The Thirty Years’ War and the decline of urban Germany - Gierok, V (University of Oxford, 2023)
This paper estimates the impact of the Thirty Years’ War (1618-1648) on urban economies in the Holy Roman Empire. It presents further evidence for Germany’s economic decline in the early modern period. Based on two novel datasets comprising data on civic wealth, public revenues, public expenditure and debt levels for 17 cities it shows that civic wealth declined by 34 percent on average. Urban communities con tributed substantially to the financing of the Thirty Years’ War: Local contributions exceeded Imperial war-financing by at least a factor of five. Over 50 percent of this expenditure came from direct wealth taxation and debt issue. This means extraction plays a substantial role in explaining the urban wealth decline during this period.